Juridical Review on Police Repressive Action in Wadas Village National Strategic Project - Hanifah Nur Ramadhanti; Dini Mardhatillah; Reyhana Nabila Ismail (IHSA Institute, 2022)
Non-violence right has been guaranteed by some regulation. However, in fact, many acts of violence are conducted by law enforcers, in this case the police, such as the cases of Wadas Village. This inspires authors to conduct research on repressive law enforcement that has violated procedures. The research method used is empirical juridical with an statue approach and a case approach. The results of this study indicate that many arbitrary arrests were accompanied by violence during the PSN implementation in Wadas Village. Executions conducted at Wadas must refer from procedural aspects so that they are in line with the protection of human rights. therefore, authors conclude there is need strict sanction from the Police to members who violate human rights. Meanwhile, the victim can apply to LPSK for compensation.